Análise do comportamento térmico de diferentes concretos de calçamento urbano frente aos cenários climáticos futuros - Rodrigues, Bruno Leandro dos Santos (2023)
Climate change is intensifying faster than predicted. Furthermore, by 2050, around 70 % of the world's population will live in urban centers, leading to greater changes in urban space and consequently an increase in the phenomenon of urban heat islands. Therefore, it is necessary to find means of mitigating the effects of warming in urban centers. One possibility for this would be to modify the urban materials usually used (waterproof and low reflectance) for materials called cool materials. Therefore, the general objective of this research was to analyze the thermal behavior of different urban paving concretes in the face of future climate scenarios, using the CNRM-ESM2-1 model and SSP3-7.0 scenario, in the periods 2021-2040, 2041-2060, 2061-2080 and 2081-2100 in the municipality of Várzea Grande, Mato Grosso. To this end, concrete boards with different traits, compositions and materials were made; the thermal behavior was analyzed, considering the internal and surface temperatures of the concrete boards and soil; the relationship between the temperatures (internal and surface) of the signs and the air temperature at a distance of 1.50 m from the ground (pedestrian level) was evaluated; the spatio-temporal simulation of climate change scenarios was carried out and analyzed through projection of average air temperature using the CNRM-ESM2-1 model and SSP3-7.0 scenario; and finally, the simulated thermal behavior was evaluated with the future projection of the materials through the correlation between the air temperature obtained in the simulation of future scenarios and the internal temperature of the material. The results demonstrated that for the urban region analyzed, and in the months analyzed, the thermal performance of materials for urban footwear is presented cooler considering proposals for cold materials aimed at increasing the reflectance and albedo of the material. Permeable materials were sometimes hotter than the reference board. Considering the future scenarios, an increase in temperature in the municipality of Várzea Grande-MT was demonstrated, around 5 ºC for the month of October, among the future scenarios. It is concluded, then, that considering the projection of the future behavior of materials, and highlighting that these are the months of greatest human discomfort and lower precipitation and relative humidity, the best proposal for urban paving would be the replacement of conventional paving with paving with proposed traits that seek to increase the reflectance of the material, such as P2, P5 and P6, which contain white cement in their composition. Given the conditions of the location and the months analyzed, it was stated that proposals focusing on permeability, considering the reduction of material heating, did not prove to be efficient either in the current scenario or in future scenarios.